Plans that go 'beep'! The emergence of methods in a mobile phone study - Lloyd, Clare (Massey University, 2008)
The methodological premise and methods used in a research project are often seen as a 'necessary ordeal' (Allen and Rumbold 2004, p. 100), and yet a clear methodological approach is the basis for all scientific research. Currently there is a substantial amount of emerging research on mobile media in various disciplines across the globe. This paper reflects upon an Australian research project nearing completion that is situated in a regional context. It outlines the theoretical premises that have underpinned the methodological practices for my doctoral research. It describes the particular methods used in a specific research project that investigates: how mobile phone use is integral in the meanings we construct through relationships with others; and, how use of the mobile phone interacts with many other communication activities. Discourse analysis has been used as a guiding methodology, and, as a distinct set of methods. Discourse analysis is understood as to be the investigation of the social construction of meaning. This definition also grounds discourse as an interrelated set of texts, and the practices of their production, dissemination, and reception, that brings an object into being? (Phillips and Hardy 2002, p. 3). The 'naturally occurring' texts collected and used as data in this project came from a range of sources. The three main methods used were: semi-structured interviews; a research journal; and the collection of cultural artefacts produced in communicative culture. During the analysis stage, the significance of the detailed research journal and some of the cultural artefacts, emerged as vital in the interpretation of interviews. These particular methods chosen for this research project intensified the reflexivity of the discursive analysis.